Rap1b-loss increases neutrophil lactate dehydrogenase activity to enhance neutrophil migration and acute inflammation in vivo - Chowdhury, Chanchal Sur; Wareham, Elizabeth; Xu, Juying; Kumar, Sachin; Kofron, Matthew; Lakshmikanthan, Sribalaji; Chrzanowska, Magdalena; Filippi, Marie-Dominique (Frontiers in Immunology, 2022)
Neutrophils are critical for host immune defense; yet, aberrant neutrophil tissue infiltration triggers tissue damage. Neutrophils are heterogeneous functionally, and adopt ‘normal’ or ‘pathogenic’ effector function responses. Understanding neutrophil heterogeneity could provide specificity in targeting inflammation. We previously identified a signaling pathway that suppresses neutrophil-mediated inflammation via integrin-mediated Rap1b signaling pathway. Here, we used Rap1-deficient neutrophils to identify pathways that specifically control pathogenic neutrophil effector function. We show neutrophil acidity is normally prevented by Rap1b during normal immune response with loss of Rap1b resulting in increased neutrophil acidity via enhanced Ldha activity and abnormal neutrophil behavior. Acidity drives the formation of abnormal invasive-like protrusions in neutrophils, causing a shift to transcellular migration through endothelial cells. Acidity increases neutrophil extracellular matrix degradation activity and increases vascular leakage in vivo. Pathogenic inflammatory condition of ischemia/reperfusion injury is associated with increased neutrophil transcellular migration and vascular leakage. Reducing acidity with lactate dehydrogenase inhibition in vivo limits tissue infiltration of pathogenic neutrophils but less so of normal neutrophils, and reduces vascular leakage. Hence, acidic milieu renders neutrophils more dependent on Ldha activity such that their effector functions are more readily inhibited by small molecule inhibitor of Ldha activity, which offers a therapeutic window for anti-lactate dehydrogenase treatment in specific targeting of pathogenic neutrophils in vivo.